JUMLAH TOTAL BAKTERI ASAM LAKTAT DAN pH PAKAN CAIR BERBAHAN BIJI ASAM UTUH PADA LAMA FERMENTASI BERBEDA - Redempta Wea; Bernadete Barek Koten; Endeyani V. Mohamad (Partner, 2021)
The aims of this research were to determine pH and the total number of lactic acid bacteria from fermented liquid tamarind seed feed. The research materials were tamarind seeds, bran, yellow corn, soybean meal, meat and bone meal, and water. The treatments were: R0: Liquid feed fermentation time (LFFT) of 0 days; R1: LFFT of 7 days; R2: LFFT 14 days; R3: LFFT 21 days; and R4: LFFT 28 days. Research variables: total number of lactic acid bacteria and pH. The results showed that the total number of lactic acid bacteria increased from 0 (fermentation time 0 days) to 5.59 x 104 CFU / ml (fermentattion time 14 days) and the pH decreased from 5.76 ± 0.11 to 3.76 ± 0.05. It was concluded that fermentation time of up to 14 days causes in the total number of lactic acid bacteria and a decrease in pH. Key Words:  Pig feed, nutrient, waste, fermentation.